Assessment of self-reported adherence among patients with type 2 diabetes in Matlala District Hospital, Limpopo Province - Sadeen A. Adegbola; Gert J.O. Marincowitz; Indiran Govender; Gboyega A.O. Ogunbanjo (AOSIS, 2016)
Introduction: Complications associated with Diabetes Mellitus are a burden to health services, especially in resource poor settings. These complications are associated with substandard care and poor adherence to treatment plans. The aim of the study was to assess the self-reported adherence to treatment amongst patients with type 2 diabetes in Matlala District Hospital, Limpopo Province. Methods: This cross-sectional study used convenience sampling with a standardised, validated questionnaire. Data were collected over 4 months, and Microsoft Excel was used for data capturing. Results: We found that 137 (70%) of the participants considered themselves adherent to their diabetes medication. Younger age (p = 0.028), current employment (p = 0.018) and keeping appointment were factors significantly associated with adherence. Reasons given for poor adherence were that the clinic did not have their pills (29%), they had forgotten to take their medication (16%) and gone travelling without taking enough pills (14%). Reasons given for poor adherences to a healthy lifestyle were being too old (29%), 22% had no specific reason, 13% struggled to motivate themselves and 10% simply forgot what to do. Sixty-eight percent of the adhered participants recommended the use of medication at meal times, 14% set a reminder, and 8% used the assistance of a treatment supporter. Conclusions and recommendations: The study revealed a higher than expected reported level of adherence to diabetes treatment. Further research is needed to assess whether self-reported adherence corresponds to the metabolic control of the patients and to improve services.